Analgesic Effects of Repetitive Transcranial Magnetic Stimulation in Patients With Advanced Non-Small-Cell Lung Cancer: A Randomized, Sham-Controlled, Pilot Study - Tang, Ying; Chen, Han; Zhou, Yi; Tan, Ming-liang; Xiong, Shuang-long; Li, Yan; Ji, Xiao-hui; Li, Yong-sheng (Frontiers in Oncology, 2022)
Objective: Current pharmacological intervention for the cancer-related pain is still limited. The aim of this study was to investigate whether repetitive transcranial magnetic stimulation (rTMS) could be an effective adjuvant therapy to reduce pain in patients with advanced non-small cell lung cancer (NSCLC). Methods: This was a randomized, sham–controlled study. A total of 41 advanced NSCLC patients with uncontrolled pain (score≥4 on pain intensity assessed with an 11-point numeric rating scale) were randomized to receive active (10 Hz, 2000 stimuli) (n = 20) or sham rTMS (n = 20) for 3 weeks. Pain was the primary outcome and was assessed with the Numeric Rating Scale (NRS). Secondary outcomes were oral morphine equivalent (OME) daily dose, quality of life (WHO Quality of Life-BREF), and psychological distress (the Hospital Depression and Anxiety Scale). All outcomes were measured at baseline, 3 days, 1 week, 2 weeks, and 3 weeks. Results: The pain intensity in both groups decreased gradually from day 3 and decreased to the lowest at the week 3, with a decrease rate of 41.09% in the rTMS group and 23.23% in the sham group. The NRS score of the rTMS group was significantly lower than that of the sham group on the week 2 (p < 0.001, Cohen’s d =1.135) and week 3 (p=0.017, Cohen’s d = -0.822). The OME daily dose, physiology and psychology domains of WHOQOL-BREF scores, as well as the HAM-A and HAM-D scores all were significantly improved at week 3 in rTMS group. Conclusion: Advanced NSCL patients with cancer pain treated with rTMS showed better greater pain relief, lower dosage of opioid, and better mood states and quality of life. rTMS is expected to be a new effective adjuvant therapy for cancer pain in advanced NSCLC patients.